THE THEME OF THE CIVIL WAR IN THE KARAKALPAK STORY OF THE 30S OF THE TWENTIETH CENTURY - Amanova Aisultan Abdirazakovna (Western European Studies, 2024)
This article deals with the theme of the civil war, the problem of the development of the Karakalpak story of the 30s of the twentieth century, the formation of literature focused on modern European artistic principles in their specific Soviet version
Keywords: Karakalpak story; civil war; theme